Categorization of indicators for performance of small and medium enterprises - Nor Mahirah, Mustapha; Sorooshian, Shahryar; Noor Azlinna, Azizan (IEOM Society, 2019)
Better understanding of the factor that influences performance at business process level is the requirement for an effective performance measurement system (PMS). Many countries develop a local PMS based on the characteristics of their Small and Medium Enterprises (SMEs). It becomes important tool to measure SMEs performance, so the business maintains in a good track. Therefore, this study aims the development of performance indicator for Malaysian SMEs. This research applied DEMATEL technique to confirm the relationship among the performance indicators besides identifying and categorize the key indicators. The result is beneficial for SME managers and advisors.